Comparing cuff pressure changes in two types of endotracheal tube - Yoldashkhan, M; Safary, F (Advances in Nursing & Midwifery, 2009)
Background Since medical devices from different manufacturers with various qualities may affect on outcome of interventions, studies regarding the correctness of them in terms of material and function have always been a major topic. Purpose This clinical trial was conducted to compare cuff pressure changes in two endotracheal tubes (ETT) in contact with nitrous oxide gas, manufactured in Iran and Malaysia. Methods 50 patients having elective surgery in Loghman Hakim Hospital and categorized in classes 1 and 2 according to American Society of Anesthesiology (ASA І, П) were randomly divided into 2 groups (27 and 23 subjects). In the first group with 27 subjects, Iranian tubes and in the other, Malasian ones were used. ETT cuffs were filled with air via minimal leak method and cuff pressures were measured by a cuff pressure indicator (VBM). It was connected to a pilot cuff until the end of anesthesia. Meanwhile, nitrous oxide 50% was prescribed for patients during anesthesia and the pressure was recorded every 20 minutes until 120 minutes of anesthesia. Results Mean and standard deviation of pressures in the cuffs of Iranian tubes before nitrous oxide administration were 96.43 and 8.23 respectively. The corresponding figures for pressures in Malaysian tubes were 17.32 and 97.4, which showed a significant difference (t=2.585, P=0.015). The standard deviation of Iranian tubes was significantly greater than Malysian ones (F=38.633, P<0.001). Conclusion It can be concluded that mean base pressures in the 2 types of tubes have no difference. This denotes that, at the beginning, there is no significant difference and the cuffs of Iranian tubes in spite of being filled with air like Malaysian ones show higher pressure difference. Mean base pressures of cuffs at different times indicate significant difference two by two. Keywords: Cuff pressure of endotracheal tube, Nitrous oxide gas.